2022
DOI: 10.1177/17474930211073387
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing vascular cognitive impairment: Current challenges and future perspectives

Abstract: Cerebrovascular disease is a major cause of cognitive decline and dementia. This is referred to as vascular cognitive impairment (VCI). Diagnosing VCI is important, among others to optimize treatment to prevent further vascular injury. This narrative review addresses challenges in current diagnostic approaches to VCI and potential future developments. First we summarize how diagnostic criteria for VCI evolved over time. We then highlight challenges in diagnosing VCI in clinical practice: assessment of severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
0
25
0
2
Order By: Relevance
“…Clinical predictors and imaging characteristics, in particular infarct location and size, have prognostic value ( Weaver et al, 2021 ), but accurate PSCI risk prediction remains challenging. Improving PSCI risk prediction is considered an important step towards developing and implementing disease-modifying therapies in patients at risk ( Biesbroek, 2022 , Vinciguerra et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical predictors and imaging characteristics, in particular infarct location and size, have prognostic value ( Weaver et al, 2021 ), but accurate PSCI risk prediction remains challenging. Improving PSCI risk prediction is considered an important step towards developing and implementing disease-modifying therapies in patients at risk ( Biesbroek, 2022 , Vinciguerra et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A major source of prognostic uncertainty after stroke is the marked heterogeneity in terms of underlying disease mechanisms, premorbid brain function and comorbidity, impact on brain connectomics, and brain plasticity ( Biesbroek, 2022 , Vinciguerra et al, 2020 ). As a consequence, two patients with an infarct that appears similar on routine brain imaging may have different cognitive outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dementia is a major complication of stroke, but the mechanisms underlying this association are not fully understood. 15 Gong et al in this month's issue investigated this question 16 using data from the PROGRESS blood pressure reduction after stroke trial. 17 Over a median follow-up of 4 years, 763 of 5888 participants (of whom 31% were women) developed cognitive decline/dementia.…”
Section: Advances In Large Artery Occlusive Stroke From Covid-19 To T...mentioning
confidence: 99%
“…11,12 Such imaging markers are providing important insights into the mechanisms of cognitive impairment in individual patient groups, and may allow targeted and more personalized treatment approaches. 9 There is also great interest in their use in predicting future risk of cognitive decline. MR-based studies have shown that scores based on both simple clinical MRI markers of SVD, 13,14 and also more advanced techniques such as diffusion tensor imaging, 15,16 may allow improved detection of which patients with stroke progress to dementia.…”
mentioning
confidence: 99%